(untitled) (Ibrahim Cardiac Medical Journal, 2015)
Background & Objective: Rabies is major public health problem in Bangladesh, although little epidemiological information is available about the disease. The present study is, therefore, intended to assess the extent of animal bite and rabies, and the status of post-exposure prophylaxis in Bangladesh. Materials & Methods: Data were retrospectively collected from clinical records and registers of patients with animal bites and rabies cases attended at IDH between January 2010 to December 2012. All the rabies cases were diagnosed clinically and were analysed using descriptive statistics. Result: Of the 276 patients of rabies patients admitted in the Infectious Disease Hospital, Mohakhali, Dhaka during the period 2009 to 2013, about 39% were 10 or <10 years old and 26.4% more than 40 years old with mean age of the patients being 26 years (range: 2-90 years). Over three-quarters (76.1%) were male (3:1). Majority (80.1%) was rural resident. The injuries were primarily inflicted by bite (92%) and rarely by scratch (8%). About 96% had injury with bleeding. Dogs were the prime biting animal (88%) followed by cat (7.2%), jackal (2.9%), mongoose (1.4%) and others (0.4%). About three-quarters (74.6%) of the animals were stray animal, followed by rabid (mad) animal (18.1%), pet (4.3%) and others (2.9%). In most cases (82.6%) the biting animal could not be traced. Most of the patients received bite in lower limbs (76.4%), were multiple (70%) and were of category III (96%). Of the total cases, only 34(12.3%) received vaccine before admission at our hospital. Of them only 9(26.5%) completed the course schedule. Half of the patients received vaccine from the pharmacy and 38.3% from Institute of Public Health (IPH). However, over 60% of the patients were uncertain about their preservation status. More than 60% of patients took more than 40 days to develop rabies following bite, 27.5% 20 - 40 days and 10.9% < 20 days. The mean interval was 72.8 days (range 10 days to 3 years). Conclusion: Rabies is usually a disease of children, male and rural resident primarily caused by bite of stray dogs. The post-exposure prophylaxis is at its worst with majority does not receive vaccine. Protection by rabies immunoglobulin is even rare. None of the patients survived of the disease. Ibrahim Cardiac Med J 2013; 3(1&2): 32-38